Path changes and injury risk in English FA Premier League soccer - Robinson, G.; O'Donoghue, P.; Nielson, P. (International Journal of Performance Analysis in Sport, 2011)
The purpose of the current investigation was to examine relationships between path changes performed by English FA Premier League soccer players, anthropometric variables and injuries reported. The study involved 25 players for whom typical path change performances were derived from at least six 90 minute matches. The players performed 39.9+13.2 sharp path changes to the side of the non-dominant leg which was significantly greater than the 35.4+12.7 sharp path changes made to the side of the dominant leg (p < .001). There was a negative association between height and the number of each type of path change (r < -.373) as well as a negative association between body mass and the number of each type of path change (r < -.287). There were no significant differences between the 10 players who missed at least one match through injury during the 2007-08 season and the 15 who did not for the frequency of any type of path change. Therefore, understanding the frequency of path changes alone is not sufficient to assess injury risk and it may also be necessary to examine the technique used when making path changes.